Comparative risk assessment of pork value chain in Nagaland, Northeast India - Deka, Ram Pratim; Grace, Delia; Lapar, Ma. Lucila; Fahrion, Anna S. (2012)
Nagaland is a state in northeast India with around 2 million inhabitants. Pork occupies an important place in the diet. Most people buy and sell pork in informal markets (called wet markets) where there is little safety and quality regulation. As part of a larger project on competitiveness of smallholder pig production in Nagaland, a study was carried out to do comparative risk assessment in representative pork meat chains. The study addressed all levels (“from stable to table”) of rural pork supply chains as well as peri-urban and rural food supply chains supplying Guwahati, the state capital. The study used participatory risk analysis, a new method for assessing and managing food safety that allows rapid and participatory assessment of hazards in resource-constrained environments. Different tools were applied including the following: (1) participatory rural appraisal to understand pig farming systems and disease problems; (2) individual questionnaires for value chain actors and consumers; (3) observational check-lists covering slaughter, transport, and retail; (4) standard microbiological tests for total bacterial contamination and fecal bacteria; and (5) rapid diagnostic tests for several pathogens in pork meat, including several bacteria, different parasites, and antibiotic residues. The data were evaluated to assess hazards as well as risk amplifying or mitigating practices. The study found high levels of food-borne hazards, many reported for the first time in Nagaland. Hygienic practices at slaughter and retail sites are very poor and there is a high risk of cross-contamination at the household level. Although some risk-mitigating practices are evident (in particular lengthy cooking of meat), other risk-enhancing practices exist (such as smoking pork in the households fires and eating without cooking). The study identifies critical control points and makes evidence-based recommendations for better management of pork-borne diseases in Nagaland.